2023
DOI: 10.1021/acs.langmuir.3c01858
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Polypropylene Nanoplastics Via Thermal Oxidation Reaction for Human Cells Responsiveness Studies

Suphatra Hiranphinyophat,
Tomoki Hiraoka,
Mako Kobayashi
et al.

Abstract: With the current worldwide increasing use of plastics year by year, nanoplastics (NPs) have become a global threat to environmental and public health concerns. Among plastics, polypropylene (PP) is widely used in industrial and medical applications. Owing to the lack of validated detection methods and standard materials for PP NPs, understanding the impact of PP NPs on the environmental and biological systems is still limited. Here, isotactic polypropylene (iPP) was fabricated into oxidized polypropylene micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…To address this issue, SPUs from polyols with fewer ether bonds are designed, and an appropriate concentration of antioxidants is added to prevent deterioration. It was revealed that the thermal oxidation of isotactic polypropylene ( it PP) could form MPs and NPs with a high carbonyl index (CI) . The responses of cells to NPs were evaluated in vitro , and a significant loss of cell viability occurred at a concentration of 100 μg/mL.…”
Section: Chemical Degradation Of Polymeric Solidsmentioning
confidence: 99%
“…To address this issue, SPUs from polyols with fewer ether bonds are designed, and an appropriate concentration of antioxidants is added to prevent deterioration. It was revealed that the thermal oxidation of isotactic polypropylene ( it PP) could form MPs and NPs with a high carbonyl index (CI) . The responses of cells to NPs were evaluated in vitro , and a significant loss of cell viability occurred at a concentration of 100 μg/mL.…”
Section: Chemical Degradation Of Polymeric Solidsmentioning
confidence: 99%